Overview of Dengue Hemorrhagic Fever Cases in North Minahasa Regency, North Sulawesi in 2018-2021 - Sarnilawati; Ririn Ali Rahmin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an endemic disease that remains a significant public health concern in Indonesia, including in North Minahasa Regency, North Sulawesi. The high morbidity and potential mortality associated with DHF underscore the importance of evaluating case trends and identifying contributing factors. In North Sulawesi, the incidence of DHF has increased in recent years, potentially driven by seasonal variations, community behavioral patterns, and suboptimal surveillance systems. Objective: This study aims to describe the trend of DHF incidence in North Minahasa Regency during 2018–2021 and to analyze the factors influencing fluctuations in case numbers over the period. Methods: A quantitative descriptive–analytical approach was employed to describe and examine the factors affecting DHF incidence in North Minahasa Regency, utilizing available surveillance data. Results: The findings show a decline in DHF cases from 329 cases in 2018 to 72 cases in 2021. This decrease reflects improvements in control measures, particularly through mosquito breeding site eradication programs and enhanced community participation. Conclusion: There was a downward trend in DHF incidence in North Minahasa Regency from 2018 to 2021, indicating strengthened disease control efforts. However, maintaining program sustainability is crucial to prevent potential resurgence in the future. Keywords: Dengue Hemorrhagic Fever, incidence rate, epidemiology, North Minahasa, Indonesia